2006
DOI: 10.1111/j.1479-6988.2006.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reduce medication errors with reference to older adults

Abstract: Background In Australia, around 59% of the general population uses prescription medi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…A flow diagram summarizes the process of review selection and identification of the primary studies within the reviews (see S1 Fig ). Thirteen reviews were included [ 25 37 ] that reported PADR data from 37 primary studies [ 38 74 ]. A citation map of the evidence demonstrates there was limited commonality of primary studies amongst the included reviews ( Fig 2 ); only five of 37 primary studies (14%) were common to two or more reviews [ 70 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A flow diagram summarizes the process of review selection and identification of the primary studies within the reviews (see S1 Fig ). Thirteen reviews were included [ 25 37 ] that reported PADR data from 37 primary studies [ 38 74 ]. A citation map of the evidence demonstrates there was limited commonality of primary studies amongst the included reviews ( Fig 2 ); only five of 37 primary studies (14%) were common to two or more reviews [ 70 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of the systematic reviews are reported in Table 3 . Eight reviews aimed to assess interventions to reduce MEs, ADRs, or PADRs [ 26 , 28 31 , 33 35 ], while five evaluated incidence, prevalence, or risk factors for MEs, ADRs, or PADRs as their stated objective [ 25 , 27 , 32 , 36 , 37 ]. Review eligibility criteria related to patient age, hospital setting, and unit of measure were highly varied.…”
Section: Resultsmentioning
confidence: 99%
“…Double-checking medications with two clinicians, most commonly nurses, is another approach recommended to help reduce medication errors (Hodgkinson, Koch, Nay, & Nichols, 2006 (Carman et al, 2013); there is a discrepancy between what nurses perceive as a person-centred approach during medication administration and their actual medication administration practices (Bolster & Manias, 2010 Garfield et al, 2016;Manias, Rixon, Williams, Liew, & Braaf, 2015). A better understanding of nurses' practices and their perceptions of medication administration in the acute care context can contribute to developing interventions tailored to increase patient involvement and potentially reduce errors in medication administration.…”
Section: Why Is This Research Needed?mentioning
confidence: 99%
“…Specific, appropriate management can reduce length of hospital stay and multiple other complications (Basic & Khoo, 2009;Day, Higgins, & Koch, 2009;Lundstrom et al, 2007;Pandharipande et al, 2005). (Hodgkinson, Koch, Nay, & Nichols, 2006) • Adherence (Yap, Thirumoorthy, & Kwan, 2016) Reconciliation can reduce drug-related problems, medication errors (Chhabra et al, 2011;Duke, Green, & Briedis, 2004;Hodgkinson et al, 2006;Pines & Hollander, 2008;Witherington, Pirzada, & Avery, 2008) and adverse events (Boockvar et al, 2004;Cornu et al, 2012). Cumulative anticholinergic or sedative effects contribute to risks for falls and cognitive impairment.…”
Section: Evidence-based Interventions and Guidelinesmentioning
confidence: 99%